Comparative catalytic activity of Mn(Salen) complexes grafted on SBA-15 functionalized with amine, thiol and sulfonic acid groups for selective aerial oxidation of limonene - Salkia, Lakshi; Srinivas, Darbha; Ratnasamy, Paul (Microporous and Mesoporous Materials, 2007)
SBA-15 molecular sieves were functionalized with propylamine, propylthiol and propylsulfonic acid groups. Mn(Salen)Cl complexes were grafted on these organo-functionalized SBA-15. The support and the type of organo-functional group influenced the electronic structure (oxidation state and redox behavior) and chemo selectivity of the Mn-complexes in the oxidation of limonene. The Mn ions were reduced from +3 to +2, the extent of this reduction on different supports decreasing in the order: SBA- 15-pr-SH > SBA- 15-prSO(3)H > SBA-15-pr-NH2- Mn(Salen)Cl supported on propylthiol-functionalized SBA-15 yielded the 1,2-limonene epoxide with 100% chemo- and regioselectivity. Higher electron density at the site of Mn ions and the consequent lower redox potential of the Mn-complexes on immobilization are the probable causes for their efficient and selective catalytic activity. Solvents, additives (N-MeIm) and co-reagents (iso-butyraldehyde), which facilitated formation of Mn2+ ions, enhance the catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction and the extent of this with different catalysts decreased in the order: SBA-l5-pr-NH2-Mn(Salen)Cl > SBA- 15-pr-SO3H-Mn(Salen)Cl > SBA- 15-pr-SH-Mn(Salen)Cl. (C) 2007 Elsevier Inc. All rights reserved